A Decision-support Service for Firefighting in Environments of Dry Tropical Forest - Araújo, Tiago Brasileiro; de Almeida, Damião Ribeiro; Lopes Filho, José Gomes; Brasil, Hicaro Ferreira; Trevisan, Ester Pequeno; Sobral, Igor Silva; de Souza, Igor P. G. F.; Queiroz, Carlos Henrique Alexandre; Soares, Ana Lícia Ferreira; Sales, Anna Beatriz Gomes; Melo Junior, Wanderley Almeida de (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
Forest fires significantly threaten the environment, society, and economy by harming biodiversity, causing economic losses, displacing communities, and impacting air and water quality. This article presents an innovative real-time monitoring application for forest fires, enhancing early detection, rapid response, and efficient coordination for Brazilian fire brigades. The app offers features such as fire location tracking, weather updates, image and video storage, and fire outbreak management. It aggregates data from various sources to provide valuable information for strategic planning and operational support.